Investigating the Coupling Effects of Momentum Wake-Buoyancy Jets in Thermohaline Stratification: A Simulation Study - Yongcheng Du; Changgeng Shuai; Feiyang Luo; Chengzhe Gao (Polish Maritime Research)
This study analyses the impact of varying temperature and salinity stratifications on the thermal characteristics of the wake through a newly established simulation model, the reliability of which is confirmed by experimental validation. In a stratified environment with sTable positive salinity but a temperature changing from positive to negative, the wake has “cold” and “hot” characteristics at the free liquid surface, respectively, and these characteristics are enhanced with an increase in the temperature gradient. In a stratified environment with a sTable positive temperature but changing positive salinity, the wake stream has “cold” characteristics at the free liquid surface, and the feature intensity has a weak positive correlation with the salinity gradient. In general, under the boundary and initial conditions studied in this paper, temperature stratification is the main factor determining the thermal characteristics of the free surface, and salinity stratification is the secondary factor. The influence of the moving induced wake on the thermal characteristics of the wake is stronger than that of the buoyant jet. In a follow-up study, we will focus on a scale analysis of the impact of stratified features on the wake, and scale extrapolation. The influence of the free surface thermal boundary layer on the wake characteristics will be another key point for investigation.